Identification of lipase producing bacteria from palm oil sewage sludge processing plant at Malimping, Banten, Indonesia - Ika Rahmatul Layly; ANJA MERYANDINI; IS HELIANTI; RIKA INDRI ASTUTI (Society for Indonesian Biodiversity, 2021)
Abstract. Layli IR, Meryandini A, Helianti I, Astuti RI. 2021. Identification of lipase-producing bacteria from palm oil sewage sludge processing plant at Malimping, Banten, Indonesia. Biodiversitas 22: 4512-4524. Lipase (triacylglycerol hydrolase E.C.3.1.1.3) is an enzyme that catalyzes the hydrolysis reaction of triacylglycerol into free fatty acids and glycerols. Lipase has broad application spectrum and unique catalytic mechanism, as one of important enzymes for industries, and almost all enzymes used for industries are originated from microbes. Identification of lipase-producing bacteria from palm oil processing sewage sludge was carried out to determine the potential of isolates and the application of lipase enzymes for industry. This study identified lipase-producing bacteria from the screening and isolation results from palm oil sewage sludge in Malimping-Banten. Two isolates were obtained from screening and isolation results. The morphological and observation and Gram staining method resulted in mlp-1 colony isolate was Gram-negative with basil cell shape, while mlp-2 colony isolate was Gram-positive with basil cell shape. Qualitative test on two isolates in tributyrin agar showed that two isolates produced clear zone or lipase enzyme. Molecular identification using 16SrRNA sequence showed that mlp-1 colony isolate was Chryseobacterium gleum, while mlp-2 colony was Bacillus velezensis. Literature study stated that Chryseobacterium gleum are pathogenic bacteria, resulting in uncontinued identification process, while Bacillus velezensis are non-pathogenic bacteria that have potential for industrial application. Identification of Bacillus velezensis was continued by performing biochemical test and inhibitory test. The continued identification results supported the molecular identification of lipase-producing enzyme for Bacillus velezensis.